KONSUMSI ONLINE SEBAGAI TINDAKAN RASIONAL BERBELANJA MASYARAKAT KOTA (Studi Pada Pegawai BRI Kantor Cabang Tuanku Tambusai Pekanbaru) - Dwi Retno Wijoyo; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In the era of communication technology development, the presence of the internet has an impact on the emergence of online consumption as a new style of consumption after previously people are more familiar with conventional transactions. This online consumption activity is a new form of communication that does not require direct face-to-face communication, but can be done separately from and to the rest of the world through the media of notebooks, computers, or mobile phones that are connected with internet access services. One of them happened to BRI Pekanbaru employees as people who were actively following technological developments, so that online consumption became an alternative consumption preferred by them. This study aims to determine how rationality of online consumption in the city of Pekanbaru, especially BRI Pekanbaru employees. The data of this study were collected through observation and documentation interview methods. Data analysis using qualitative descriptive analysis. The theory used in this research is the theory of rationality and personalization. The results of this study are that there is an online consumption phenomenon that occurs in urban communities, especially BRI Pekanbaru employees. Online shopping has now become a shopping style trend with the urban people's online consumption behavior taking place through the purchase decision process and can be seen with elements of consumer behavior analysis. Online consumption transactions are carried out by urban communities because they are based on rational motives that emphasize efficiency and effectiveness in achieving certain goals such as meeting needs and lifestyles. Keywords: Online consumption, Rationality, McDonaldization.